OPTIMALISASI ZAKAT TERHADAP PENGENTASAN KEMISKINAN (STUDI PADA BAZNAS KOTA MAKASSAR) - Astika, Sri; Basalamah, Salim; Amiruddin, Amiruddin (Jurnal Ar-Ribh, 2021)
The purpose of this study is to determine the management of zakat, efforts to optimize zakat management for poverty alleviation and to determine the results of the implementation of zakat on poverty reduction in the city of Makassar. The type of this research is qualitative research. This research conducted at Baznas Makassar City. Types of data are primary and secondary data sourced from informants and documentation. Data collection techniques with interview and documentation methods. The results of the study found that the zakat management mechanism at the Makassar City Baznas begins with planning, organizing and implementing the collection, distribution and utilization of zakat. Makassar City Baznas efforts in optimizing zakat management towards poverty alleviation are carried out by distributing zakat through consumptive zakat distribution patterns (short-term benefits) and productive zakat (zakat utilization) in accordance with the rules of Islamic law. The implementation of productive zakat utilization in the form of providing funds as business capital to mustahik. With the utilization of zakat, it is able to exclude 51 people from the poor population based on BPS. However, this is not considered optimal because it still does not meet the target of 67 people or 76%.Keywords: Optimization, Zakat Management, Poverty Alleviation, Maqasyid Syariah